Produce and Protection: Covent Garden Market, the Socioeconomic Elite, and the Downtown Core in London, Ontario, 1843–1915 - Gouglas, Sean (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1996)
This article evaluates the historical significance of the farmers' market in London, Ontario, the centre-piece of the city's booster activity. The author uses a systematic analysis of mercantile credit reports, city directories, and assessment rolls, combined with anecdotal evidence from local newspapers, diaries, and council records. The paper argues that Covent Garden Market initiated and entrenched economic and social patterns of development that privileged a minority of the city's merchants. Capitalizing on their initial advantage of location, these merchants and councillors maintained their hold on the market's monopoly of place by rigorously enforcing and tightening market regulations, maintaining a constant police presence, and petitioning the town for a rigid enforcement of the market by-laws. The market enhanced the economic influence of this elite under the pretense of protecting the general populace from unscrupulous vendors. The market proved a social and economic arena, a centre of urban and rural relations, outside of which economic failure proved a real possibility.